PENINGKATAN KEMAMPUAN LITERASI INFORMASI BERDASARKAN STANDAR ACRL MELALUI PEMANFAATAN MULTIMEDIA BAGI GURU SEKOLAH DASAR - Dyoty Auliya Vilda Ghasya,; Gio Mohamad Johan; Lili Kasmini (Jurnal Visipena, 2018)
Information literacy is a skill needed to search, analyze and utilize information. So that information literacy is a very important ability that is owned by a person, especially in the world of education, in this case elementary school teachers because at this time all people are faced with various types of information resources that are developing very rapidly, but not necessarily all the information that is available and created can be trusted and in accordance with the information needs of information seekers. Based on direct observations made by the team proposing the Community Partnership Program (PKM) in partner primary schools found data and information that the information literacy skills of elementary school teachers are still below the standards of the Association of College and Research Libraries (ACRL). This information literacy standard lists a number of abilities used in determining a person's ability to understandinformation. Seeing the problem of information literacy ability of partner elementary school teachers is still below the ACRL standard, the proposer team will utilize multimedia as one solution to improve information literacy skills of partner primary school teachers. The advantage of using multimedia the most prominent is interactivity which means that this media inherently forces users to interact with the material. This interaction varies from the simplest to the complex. This program will be implemented for elementary school teachers in Aceh Besar District. The objectives of this program are (1) through this mentoring activity it is believed that it can increase the repertoire of knowledge of primary school teachers regarding information literacy capacity building programs, (2) Through mentoring activities will improve elementary school teacher information literacy skills based on the standards of the Association of College and Research Libraries (ACRL) through multimedia utilization. (3) Develop the skills of elementary school teachers in designing simple information literacy media that are easy to make and applicable to the learning presented. Abstrak Literasi informasi merupakan suatu keterampilan yang diperlukan untuk mencari, menganalisis dan memanfaatkan informasi. Sehingga literasi informasi merupakan kemampuan yang sangat penting dimiliki seseorang terutama pada dunia pendidikan, dalam hal ini guru sekolah dasar karena pada saat ini semua orang dihadapkan dengan berbagai jenis sumber informasi yang berkembang sangat pesat, namun belum tentu semua informasi yang ada dan diciptakan tersebut dapat dipercaya dan sesuai dengan kebutuhan informasi para pencari informasi. Berdasarkan observasi secara langsung yang dilakukan oleh tim pengusul Program Kemitraan Masyarakat (PKM) pada sekolah dasar mitra ditemukan data dan informasi bahwa kemampuan literasi informasi guru sekolah dasar masih dibawah standar Association Of College and Research Libraries (ACRL). Standar literasi informasi ini berisi daftar sejumlah kemampuan yang digunakan dalam menentukan kemampuan seseorang dalam memahami informasi. Melihat permasalahan kemampuan literasi informasi guru sekolah dasar mitra masih dibawah standar ACRL tersebut, maka tim pengusul akan memanfaatkan multimedia sebagai salah satu solusi untuk meningkatkan kemampuan literasi informasi guru sekolah dasar mitra. Keunggulan dari pemanfaatan multimedia yang paling menonjol adalah interaktivitas yang artinya media ini secara inheren memaksa pengguna untuk berinteraksi dengan materi. Interaksi ini bervariasi dari yang paling sederhana hingga yang kompleks. Program ini akan dilaksanakan pada guru sekolah dasar di Kabupaten Aceh Besar. Adapun tujuan dari program ini adalah (1) Melalui kegiatan pendampingan ini diyakni dapat menambah khasanah pengetahuan guru sekolah dasar mengenai program peningkatan kemampuan literasi informasi, (2) Melalui kegiatan pendampingan akan meningkatkan kemampuan literasi informasi guru sekolah dasar berdasarkan standar Association of College and Research Libraries (ACRL) melalui pemanfaatan multimedia. (3) Mengembangkan keterampilan guru sekolah dasar dalam mendesain media literasi infromasi sederhana yang mudah dibuat dan aplikatif dengan pembelajaran yang disajikan. Kata Kunci: Literasi Informasi, Standar ACRL, Multimedia